PENGAWASAN PERIZINAN PERENCANAAN TATA RUANG PARIWISATA ALAM DALAM MENJALANKAN SISTEM KEAMANAN PERLINDUNGAN LINGKUNGAN HIDUP - Ar Rasyid, M. Afif (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2025)
Environmental law is a science that provides guidelines for putting into practice the use of natural resources possessed. Indonesia itself has abundant natural resources and quite a few of These natural resources serve as regions that are popular tourist destinations. Spatial planning law plays a role in carrying out enforcement actions regarding the tourist layout whether it is in accordance with the AMDAL as well as safety, security and the form of ecotourism. Oversight of the creation of plans for spatial planning must involve cooperation and relationship between regional and national governments. The plan for safeguarding tourists is actually regulated and implemented firmly and clearly with the existence of legal regulations to provide guidelines for legal certainty. Relevant laws should be reviewed such as the 2009 Law No. 10 on Tourism to find out whether there are aspects of legal protection and security for tourists. This protection is very important for the security and safety of tourists, as well as protecting their dignity, lives and property. The aspect of legal protection for tourists must be considered in Indonesia as a legal country. Many natural tourism locations in dangerous places must be given special attention. Ecotourism development must pay attention to ecotourism principles and continuity between the environment, society and economic movements that occur before and during ecotourism. The method used is normative juridical employing secondary legal documents or literature studies as sources of legal information.